A new multiplex RT-qPCR method for the simultaneous detection and discrimination of Zika and chikungunya viruses - Broeders, Sylvia (Int J Infect Dis, 2020)
OBJECTIVE: The re-emergence and spread of tropical viruses to new areas has raised a wave of concern worldwide. In order to treat patients at an early stage and prevent the diffusion of an outbreak, early diagnosis, and therefore fast and adequate detection, is needed. To this end, a multiplex reverse transcription real-time polymerase chain reaction TaqMan method was designed to detect Zika (ZIKV) and chikungunya (CHIKV) viruses simultaneously. METHODS: Two methods targeting different genome segments were selected from the literature for each virus. These were adapted for high genome coverage and combined in a four-plex assay that was thoroughly validated in-house. The SCREENED tool was used to evaluate the sequence coverage of the method. RESULTS: The full validation approach showed that the new four-plex method allows the specific and sensitive identification and discrimination of ZIKV and CHIKV in routine samples. The combination of two targets per virus allowing almost 100% coverage of about 500 genomes is shown for the first time. CONCLUSIONS: PCR is a reliable user-friendly technique that can be applied in remote areas. Such multiplex methods enable early and efficient diagnosis, leading to rapid treatment and effective confinement in outbreak cases. They may also serve as an aid for surveillance, and the full validation permits easy method-transfer allowing worldwide harmonization.